Obesity: a chronic relapsing progressive disease process. A position statement of the World Obesity Federation. (10th May 2017) - Bray, G.A.; Kim, K.K.; Wilding, J.P.H.
Summary: This paper considers the argument for obesity as a chronic relapsing disease process. Obesity is viewed from an epidemiological model, with an agent affecting the host and producing disease. Food is the primary agent, particularly foods that are high in energy density such as fat, or in sugar‐sweetened beverages. An abundance of food, low physical activity and several other environmental factors interact with the genetic susceptibility of the host to produce positive energy balance. The majority of this excess energy is stored as fat in enlarged, and often more numerous fat cells, but some lipid may infiltrate other organs such as the liver (ectopic fat). The enlarged fat cells and ectopic fat produce and secrete a variety of metabolic, hormonal and inflammatory products that produce damage in organs such as the arteries, heart, liver, muscle and pancreas. The magnitude of the obesity and its adverse effects in individuals may relate to the virulence or toxicity of the environment and its interaction with the host. Thus, obesity fits the epidemiological model of a disease process except that the toxic or pathological agent is food rather than a microbe. Reversing obesity will prevent most of its detrimental effects.